2010
DOI: 10.1007/s00464-010-0909-1
|View full text |Cite
|
Sign up to set email alerts
|

Short- and long-term costs of laparoscopic colectomy are significantly less than open colectomy

Abstract: We demonstrate both short- and long-term financial benefits of LC in a high-volume tertiary care hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 27 publications
(32 reference statements)
3
2
0
Order By: Relevance
“…reported a significant reduction in complication rates after laparoscopy, several other studies support our finding . Like most other studies, we found that laparoscopic surgery has significantly shorter hospital stay …”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…reported a significant reduction in complication rates after laparoscopy, several other studies support our finding . Like most other studies, we found that laparoscopic surgery has significantly shorter hospital stay …”
Section: Discussionsupporting
confidence: 91%
“…Although Lacy et al 16 reported a significant reduction in complication rates after laparoscopy, several other studies support our finding. [17][18][19][20] Like most other studies, we found that laparoscopic surgery has significantly shorter hospital stay. 17,20 Our study also largely antedates the techniques of endoscopic mucosal resection (EMR) and endoscopic submucosal dissection (ESD).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…We attribute this to the select group of patients whose conditions in an emergent setting often required additional investigations and medications, closer monitoring in specialized wards, and longer hospital stays compared to patients who underwent elective colectomies. We believe that the short- and the long-term financial benefits that were seen in elective laparoscopic colectomies should also be seen in the emergency setting [15]. …”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22][23][24] This is also reinforced by the successful implementation of laparoscopy into surgical training programs such as FLS (Fundamentals of Laparoscopic Copyright © 2011 Lippincott Williams & Wilkins. Unauthorized reproduction of this article is prohibited.…”
Section: Natural Orifice Transluminal Endoscopic Surgery: Where Shouldmentioning
confidence: 96%